2009
DOI: 10.1007/s00595-009-4003-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal hamartoma of the liver originating in the caudate lobe with t(11;19)(q13;q13.4): Report of a case

Abstract: We herein report the case of a 35-month-old female child presenting with mesenchymal hamartoma of the liver (MHL), with t(11;19)(q13;q13.4) originating in the caudate lobe. This case is the eighth known description of a cytogenetic abnormality in mesenchymal hamartoma of the liver. It is similar to the seven cases previously reported, in that one of the breakpoints involves the chromosome band 19q13.3 or 19q13.4, but it is the first report of an abnormality originating in the caudate lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The frequent documentation of chromosomal rearrangements involving chromosome 19q13.4 in sporadic HMH suggests involvement of 1 or more genes at this specific locus [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The most frequently reported rearrangements are translocations between chromosomes 11q and 19q13.4, one of which was characterized and *Corresponding author, e-mail: raj.kapur@seattlechildrens.org shown to involve the MALAT1 gene at 11q13 and a site at 19q13.4, which initially did not contain an identifiable gene [26].…”
Section: Introductionmentioning
confidence: 99%
“…The frequent documentation of chromosomal rearrangements involving chromosome 19q13.4 in sporadic HMH suggests involvement of 1 or more genes at this specific locus [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The most frequently reported rearrangements are translocations between chromosomes 11q and 19q13.4, one of which was characterized and *Corresponding author, e-mail: raj.kapur@seattlechildrens.org shown to involve the MALAT1 gene at 11q13 and a site at 19q13.4, which initially did not contain an identifiable gene [26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this aberration occurs late in embryogenesis, because the liver adjacent to the lesion has a normal architecture [2]. Others assume that it is a true neoplastic process; indeed, cytogenetic abnormalities have been found in some cases of liver hamartom as chromosomal translocations involving a break in the long arm of chromosome 19 (band 19q13.4) [3] Mesenchymal hamartoma of the liver occurs in the right liver lobe in approximately 75% of all cases,others occur in the left lobe; the tumor involvement of both lobes is less than 5% [4].Mesenchymal hamartoma of the liver: a systematic review. [5] Excision may be by conventional hepatic resection or by nonanatomical excision with a small margin of normal liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed translocation did not lead to any fusion genes. (11)t (11;19)(q13;q13), der (19)t (11;19) The chromosomal translocation t(11;19)(q13;q13) has also been reported as an acquired, recurrent genomic rearrangement in mesenchymal hamartoma of the liver, which is a rare benign tumor in children (23)(24)(25)(26)(27)(28). Molecular studies of such tumors showed that the t(11;19)(q13;q13) of mesenchymal hamartoma was associated with deregulation of gene expression (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%